Compressive response and energy absorption of all-composite sandwich panels with channel cores. (1st June 2022) - Zhu, Keyu; Zheng, Xitao; Zhang, Cong; Chen, Niu; Han, Yagang; Yan, Leilei; Quaresimin, M.
Abstract: The novel all-composite sandwich panel with channel core was proposed for simultaneous compressive strength and energy absorption characteristic subjected to quasi-static out-of-plane compression. The structure was composed of carbon fiber reinforced polymer (CFRP) face-sheets and channel core. The compressive responses and deformation mechanism of the proposed structure were studied by the method of experiment and finite element analyses (FEA). Meanwhile, the sandwich panel with traditional corrugated core was also considered and fabricated, as comparison. In contrast to sandwich panel with traditional corrugated core, the proposed structure exhibited a progressive crushing mode, indicating the compressive strength and specific energy absorption were increased by 209.03% and 718.32%. Compared with different damage modes, the damage mode of delamination makes sandwich panel with channel core exhibit much better compressive strength and specific energy absorption. Besides, the method of foam filling is also considered to improve structural efficiency further by offering support and constraint of boundary condition. The compressive strength and specific energy absorption of foam filled sandwich panel with channel increase by 89.19% and 29.28% respectively. Due to good structural efficiency, the proposed structure had wide potential applications in lightweight fields.